Plant root exudation under drought: implications for ecosystem functioning - Williams, Alex; de Vries, Franciska T. (The New phytologist, 2020)
Root exudates are a pathway for plant–microbial communication and play a key role in ecosystem response to environmental change. Here, we collate recent evidence that shows that plants of different growth strategies differ in their root exudation, that root exudates can select for beneficial soil microbial communities, and that drought affects the quantity and quality of root exudation. We use this evidence to argue for a central involvement of root exudates in plant and microbial response to drought and propose a framework for understanding how root exudates influence ecosystem form and function during and after drought. Specifically, we propose that fast-growing plants modify their root exudates to recruit beneficial microbes that facilitate their regrowth after drought, with cascading impacts on their abundance and ecosystem functioning. We identify outstanding questions and methodological challenges that need to be addressed to advance and solidify our comprehension of the importance of root exudates in ecosystem response to drought.